Integrating Innovation with Integrity: Navigating the Humanistic and Ethical Dimensions of the Fourth Industrial Revolution - Khuat, Nga Thi (Griot : Revista de Filosofia, 2025)
The Fourth Industrial Revolution (4IR) marks a transformative period in which the convergence of biological, digital, and physical technologies redefines human existence and societal structures. This paper critically examines the philosophical, ethical, and socio-political implications of these advancements, advocating for an integrative approach that aligns rapid technological innovation with enduring humanistic values. By addressing the potential for both human advancement and the exacerbation of social inequalities, the study emphasizes the importance of ethical reflection, robust regulatory frameworks, and educational reforms. It further explores the profound changes in work, identity, and community dynamics, calling for proactive policies to ensure equitable access to the benefits of 4IR while preserving human diversity. Ultimately, this analysis calls for a responsible and ethical engagement with emerging technologies to foster a future that promotes justice, human dignity, and planetary sustainability.